PO 132 - Síndrome de implantação de cimento – um diagnóstico presuntivo - Portugalyan, Mihran; Sousa, Bárbara; Pinto, Sofia; Godinho, Pedro (Journal of the Portuguese Society of Anesthesiology, 2023)
x